Quantification of urine 17-ketosteroid sulfates and their age correlations. Issue 3 (2002) - Jia Jia, Qi Qi; Hong Hong, Mei-Feng Mei-Feng; Pan Pan, Zhao-Xing Zhao-Xing; Ritter Ritter, Cheryl Cheryl; Vance Vance, Susan Susan; Cortes-Guzman Cortes-Guzman, Miriam Miriam; Cherniske Cherniske, Stephen Stephen
Abstract : Dehydroepiandrosterone (DHEA) is a steroid secreted primarily by the adrenal gland and plays an important role as the primary precursor of many important sex steroids. The negative correlation between age and the secretion of DHEA (I) and in its sulfate form (II, DHEA-S) has been documented in human studies. Serum DHEA (I) and/or DHEA-S (II) levels have been associated with central nervous system function, immunity, cardiovascular functions, insulin sensitivity, and body composition. A high-performance liquid chromatography/ion trap mass spectroscopic method with sonic spray ionization (SSI) for the quantification of individual and total urinary 17-ketosteroid sulfates was developed. This quantification method had broad linearity range, low detection limit and high throughput. The amount of 17-KS-S, normalized by creatinine, in urine secreted over 24 hours versus that in early morning urines was found inversely correlated to age for both genders.